Associations between gene polymorphisms and treatment outcomes of methotrexate in patients with juvenile idiopathic arthritis. (April 2018) - Chen, Yuehong; Zou, Kun; Sun, Jianhong; Yang, Yuan; Liu, Gang
Aim: Performance of a meta-analysis with respect to the genetic predictors of methotrexate (MTX) treatment outcomes, efficacy and toxicity, in patients with juvenile idiopathic arthritis (JIA).Methods: Databases of OVID MEDLINE and OVID EMBASE were searched to collect the studies addressing correlations between gene polymorphisms and efficacy and/or toxicity in MTX-treated JIA patients. Pooled odds ratios (ORs) with 95% CIs were estimated in allelic, recessive and/or dominant models.Results: With regards to efficacy, the C677T (rs1801133) polymorphism in MTHFR was associated with nonresponse to MTX treatment in a recessive model (OR: 0.40; 95% CI: 0.19–0.84). For associations with toxicity, the MTHFR C677T (rs1801133) polymorphism was associated with presenting overall adverse events in an allelic model (OR: 1.54; 95% CI: 1.07–2.22) and a dominant model (OR: 1.70; 95% CI: 1.08–2.68).Conclusion: C677T (rs1801133) polymorphism in MTHFR predicts nonresponse and/or adverse effects of MTX treatment in JIA patients.